Relationship Domain of Form Six Teachers Thinking in Teaching with External Factors of Form Six Teachers - bin Pet, Mokhtar; Hj Sihes, Ahmad Johari (Institute of Advanced Engineering and Science, 2015)
This study aimed to examine the external factors of form six teachers who can influence thinking domain form six teachers in their teaching. This study was conducted using a quantitative approach using questionnaires. A total of 300 form six teacher schools in Johor were chosen as respondents. The findings were obtained as student background factors are the most important factors that influence the thinking domain of form six teachers with a mean value of 4.54 and the domain of thinking is that teachers' expectations domain is the most important with the 4:54. Relation to external factors form six teachers with thinking domain form six teachers in the teaching of significant positive classroom atmosphere factors with r = .524, school goals with r = .405, needs of students with r = .454 and students background with r = .423. This study will help the Ministry of Education to raise the standards of form six education.